Pseudmonas cannabina pv. alisalensis TrpA Is Required for Virulence in Multiple Host Plants - Sakata, Nanami; Ishiga, Takako; Ishiga, Yasuhiro (Frontiers in Microbiology, 2021)
Pseudomonas cannabina pv. alisalensis (Pcal) causes bacterial leaf spot and blight of Brassicaceae and Poaceae. We previously identified several potential Pcal virulence factors with transposon mutagenesis. Among these a trpA mutant disrupted the tryptophan synthase alpha chain, and had an effect on disease symptom development and bacterial multiplication. To assess the importance of TrpA in Pcal virulence, we characterized the trpA mutant based on inoculation test and Pcal gene expression profiles. The trpA mutant showed reduced virulence when dip- and syringe-inoculated on cabbage and oat. Moreover, epiphytic bacterial populations of the trpA mutant were also reduced compared to the wild-type (WT). These results suggest that TrpA contributes to bacterial multiplication on the leaf surface and in the apoplast, and disease development. Additionally, several Brassicaceae (including Japanese radish, broccoli, and Chinese cabbage) also exhibited reduced symptom development when inoculated with the trpA mutant. Moreover, trpA disruption led to downregulation of bacterial virulence genes, including type three effectors (T3Es) and the phytotoxin coronatine (COR), and to upregulation of tryptophan biosynthesis genes. These results indicate that a trade-off between virulence factor production and Pcal multiplication with tryptophan might be regulated in the infection processes.